Neuropathic pain inhibitor, RAP-103, is a potent inhibitor of microglial CCL1/CCR8. (October 2018) - Noda, Mami; Tomonaga, Daichi; Kitazono, Kota; Yoshioka, Yusaku; Liu, Jiadai; Rousseau, Jean-Philippe; Kinkead, Richard; Ruff, Michael R.; Pert, Candace B.
Abstract: Chemokine signaling is important in neuropathic pain, with microglial cells expressing chemokine (C-C motif) receptor CCR2, CCR5 and CCR8, all playing key roles. In the previous report (Padi et al., 2012), oral administration of a short peptide, RAP-103, for 7 days fully prevents mechanical allodynia and inhibits the development of thermal hyperalgesia after partial ligation of the sciatic nerve in rodents. As for the mechanism of the inhibiting effect of RAP-103, it was speculated to be due to dual blockade of CCR2 and CCR5. We report here that RAP-103 exhibits stronger antagonism for CCR8 (half maximal inhibitory concentration [IC50 ] 7.7 fM) compared to CCR5 (IC50 < 100 pM) in chemotaxis using primary cultured mouse microglia. In addition, RAP-103 at a concentration of 0.1 pM completely inhibits membrane ruffling and phagocytosis induced by chemokine (C-C motif) ligand 1 (CCL1), an agonist for CCR8. It has been shown that CCL1/CCR8 signaling is important in tactile allodynia induced by nerve ligation. Therefore, CCR8, among other chemokine receptors such as CCR2/CCR5, could be the most potent target for RAP-103. Inhibitory effects of RAP-103 on plural chemokine receptors may play important roles for broad clinical use in neuropathic pain treatment. Highlights: RAP-103, a stabilized analog of DAPTA and a CCR5 entry inhibitor, is a potent inhibitor of CCR8. Oral administration of RAP-103 for 7 days is reported to prevent mechanical allodynia. RAP-103 exhibits stronger antagonism for CCR8 compared to CCR5 in chemotaxis using primary cultured mouse microglia. Therefore, CCR8, among other chemokine receptors such as CCR2/CCR5, could be the most potent target for RAP-103.